178 Relationships Between Sow Blood Glucose Levels on Day of Farrowing and Sow and Litter Parameters. (7th May 2021) - Yeich, Brian P; Rivas, Rafael Ovidio Bautista; Willard, Naomi C; Vande Pol, Katherine D; Morris, Jenny R; Espinal, Alicia Olivo; Moest, Nicole K; Shull, Caleb M; Ellis, Michael
Abstract: Low blood glucose levels at the start of farrowing have been associated with increased farrowing duration and stillbirth rate. This study evaluated changes in sow blood glucose (BG) on the day of farrowing and investigated relationships between sow and litter parameters and BG. The study was carried out over 12 h from 0600h (time of last feeding) on the day sows were induced to farrow (d 115 of gestation) as a cross-sectional survey using 42 sows/gilts of which 32 farrowed. Blood samples (1.2 μL) were collected from an ear vein of each sow every 2 h from 0600 h; glucose was measured using a glucometer (Accuchek Aviva; Roche Diabetes Care, Inc., Indianapolis, IN). Sow parameters recorded included parity, body condition score (BCS: 1 = extremely thin to 5 = extremely fat), number of piglets born, total litter birth weight, and farrowing duration. Linear relationships between sow parameters and BG were developed using PROC REG of SAS. Sows that farrowed had similar (P > 0.05) BG to those that did not (84.4 vs. 86.8 mg/dL; SEM 1.76). Regression relationships between sow parameters and BG were generally weak (adjusted R 2 ≤ 0.20). There was no effect (P > 0.05) of time after feeding, time after start of farrowing, or time interval between piglet births on BG. Average BG levels increased linearly (P < 0.05) with sow BCS (7.6 mg/dL/BCS; SE 2.63) but decreased linearly (P < 0.05) with sow parity (-2.5 mg/dL/litter; SE 0.96), litter size (-0.8 mg/dL/piglet; SE 0.28), litter weight (-0.06 mg/dL/kg; SE 0.26), and farrowing duration (-1.8 mg/dL/h; SE 0.82). In contrast to previous research, changes in BG from last feed to start of farrowing (which ranged from 0 to 9 h) and relationship with other sow and litter parameters were relatively limited.